Study of the optical properties of SiO2, and Al2O3 films deposited by electron beam technique - Shakouri, Reza (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Al2O3 and SiO2 thin films have been prepared by electron beam evaporation at different oxygen flows. The influences of oxygen partial pressure on optical properties of Al2O3 and SiO2 thin films have been studied. We have coated Al2O3 and SiO2 without some oxygen background in the chamber. The results show that Al2O3 thin film does not have absorption even though it is coated without oxygen background in the chamber. On the other hand, without oxygen flow, SiO2 thin film has some absorption. The packing density of the samples is studied by change in the spectrum of a coating with humidity